Development of Geodatabase of Drainage and Watergate Facilities in Muar - mohamad firdaus joo, mohamad farhan; Mohd Bukari, Saifullizan (Recent Trends in Civil Engineering and Built Environment, 2021)
In respect to social, environmental and economic perspective, flood has been one of the most destructive disaster in Muar. A flood is a situation in which water flows overspill the river channel system. The current drainage system has not been able to accumulate and drain more trends than the standard process. This was due to the tremendous and continuous rain that led to excessive amounts of river water than usual thus overflowing to a lower area. The drainage basin is a catchment area for rainwater to flow into lakes, rivers or swamps. Flood analysis can be greatly helped by using the advanced technology of the Geographic Information System (GIS). Aside from that, a GIS system is a highly strong tool utilized in hydrological engineering to assist engineers and planners in imagining the real-world scenario of flood occurrences, conducting flood analyses, solving problems, and making reasonable, accurate, and effective decisions.